The CAPITAL ASSET PRICING MODEL ANALYSIS (CAPM) IN STOCK INVESTMENT DECISION MAKING Sri Sudiarti - Sri Sudiarti; Doni (LKP DCI, 2024)
This research aims to determine various stock investments with the Capital Asset Pricing Model (CAPM) method, to help investors pick efficient and inefficient stock. The population in this study are all companies listing in Jakarta Islamic Index. The sampling technique used was purposive sampling method and acquired 16 stocks. The results show that there was positive relationship or non linear relationship between systematic risk and expected return. There are 13 stocks included on efficient and investment decisions should be taken by investors was to buy efficient stocks, while there are 3 stocks included on inefficient and investment decisions should be taken by investors was to sell inefficient stocks.